Yamamotoyama: Tradition and change in a 300-year-old Shinise - REB, Jochen (Institutional Knowledge at Singapore Management University, 2023)
Kaichiro Yamamoto is the 10th generation president of Yamamotoyama (YMY), a tea company that is one of Japan’s revered shinise: companies that have operated for more than a century. His only child, Nami Yamamoto, is expected to serve as the first female president of the company after him. YMY had gradually expanded the business overseas to Brazil and the US, and Nami Yamamoto had taken charge of overseas operations. YMY had been a household name in Japan and enjoyed the great reputation of a shinise. At the same time, it faced a changing business environment in which gift giving was becoming less common, reducing demand for YMY’s expensive and fine products. Each generation encountered different challenges. Along with it came the tensions among growth, stability, risk-taking, and sustainability. How could the leaders ensure the survival and sustainability of the company? This case may be used for graduate, postgraduate and executive education classes. Learning objectives for the students are to raise student awareness of cultural influences on leadership and strategic decision-making; highlight a business model that emphasise business continuation instead of profit maximisation and provide an opportunity to discuss and draw lessons from how the long-term orientation of shinise family businesses may support sustainability.